Cybernethisms : Aldo Giorgini's computer art legacy - García Bravo, Esteban (Purdue University Press, 2015)
Working extensively as both artist and scientist, Aldo Giorgini (1934-1994) was one of the first computer artists to combine software writing with early printing technologies. His innovative process involved producing pen-plotted drawings that were embellished by painting, drawing, photography, and screen printing. This biography is the first to uncover the remarkable work and life of an underappreciated artist, providing insights into the innovative methods and computerized techniques he used to weave creations that seamlessly combined technological sophistication with artistic sensibility. Bu.